2005
DOI: 10.1159/000082648
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcomes in Severe Preeclampsia-Eclampsia with and without HELLP Syndrome

Abstract: Objective: Our purpose was to find out and compare perinatal outcomes in pregnancies complicated by severe preeclampsia-eclampsia with and without HELLP syndrome. Methods: Clinical and laboratory findings, and perinatal-neonatal outcomes of all pregnants with severe preeclampsia, eclampsia and HELLP have been prospectively recorded. Results were compared by means of Student’s t test, χ2 analysis and Fisher’s exact test as appropriate. Results: Among 367 consecutive severe preeclampsia, 106 (29%) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
48
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 26 publications
6
48
0
8
Order By: Relevance
“…However, there are further studies showing that gestational age was more effective than maternal disease for perinatal outcomes (7,(17)(18)(19). In two studies, neonatal death rates were not different between HELLP syndrome and severe preeclampsia at the same stage of gestation (7,20). In our study, women were divided into two gestational age groups and perinatal outcomes were evaluated separately in these two groups.…”
Section: Discussionmentioning
confidence: 72%
“…However, there are further studies showing that gestational age was more effective than maternal disease for perinatal outcomes (7,(17)(18)(19). In two studies, neonatal death rates were not different between HELLP syndrome and severe preeclampsia at the same stage of gestation (7,20). In our study, women were divided into two gestational age groups and perinatal outcomes were evaluated separately in these two groups.…”
Section: Discussionmentioning
confidence: 72%
“…These include: 1) Immediate delivery which is the primary choice at 34 weeks' gestation or later.2) Delivery within 48 hours after evaluation, stabilization of the maternal clinical condition and corticosteroid (CS)treatment. At 27 to 34 weeks of gestation, this option appears appropriate and rational for the majority of cases [21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…The perinatal mortality rate related to HELLP syndrome is between 7.4% and 34%. 18 Neonatal thrombocytopenia occurs in between 15%and 38% cases and is significant risk factor for both intraventricular hemorrhage and long term neurological complication. 18 In the present study neonatal mortality was seen in 17.64% babies with HELLP syndrome 25% with partial HELLP syndrome which is comparable to above studies.…”
mentioning
confidence: 99%
“…18 Neonatal thrombocytopenia occurs in between 15%and 38% cases and is significant risk factor for both intraventricular hemorrhage and long term neurological complication. 18 In the present study neonatal mortality was seen in 17.64% babies with HELLP syndrome 25% with partial HELLP syndrome which is comparable to above studies. When perinatal results were evaluated in Selahattin et al study, it was found that HELLP syndrome cases had six times more risk of neonatal mortality than severe preeclampsia cases even though it was statistically not significant.…”
mentioning
confidence: 99%
See 1 more Smart Citation